Familiarity Factors of Street Features in Pedestrian Wayfindings (International Journal of Built Environment and Sustainability, 2018)
From an origin point to a destination point, good wayfinding process requires familiar recognition on the street environment. However, the unclear reasons of identifying street features to determine a route to the destination influences a pedestrian to select the wrong turn, walk in longer distance, and lost his direction. This paper aims to identify the factors that influence pedestrian familiarity, familiar or unfamiliar, in people wayfinding. Two hundred questionnaires were collected in Teluk Intan, Perak, Malaysia. Quotations from 30 interviews were used to triangulate the findings. Factor analysis available in IBM SPSS version 21 was used in exploring the familiarity factors for wayfinding. The finding suggests three factors influenced pedestrian to familiar with the street environment, which the factors are characteristic, attraction, and interest of street features. While, the duplication design of street features, error in defining the position of street features and form similarity of street features influence pedestrian to become unfamiliar with the street environment. This paper implies that the physical form of street features gives impact to pedestrian familiarity. Consideration of the three factors that influence pedestrian to familiar with the environment can improve how pedestrian experience in street network especially wayfinding.
Keywords: Affecting factors; Pedestrian familiarity; Wayfinding; Street environment; Street features